1990
DOI: 10.1161/01.atv.10.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA polymorphism at the apolipoprotein B gene locus with coronary heart disease and serum very low density lipoprotein levels.

Abstract: The role of genetic variation at the 3' end of the apolipoprotein B gene locus In the development of coronary heart disease and the regulation of the serum levels of various lipoprotelns was studied by using two common restriction fragment length polymorphisms detected with the enzymes Xba I and EcoR I. A group of 106 male patients with coronary heart disease and 118 matched controls of Austrian origin were Investigated. The frequency of the R2 allele of the EcoR I polymorphism at cDNA position 12 669 defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…This could contribute to the association, in human populations, between CAD and the E" allele, as coronary atherosclerosis is related positively to serum cholesterol concentration. 7 Although a statistically significant association between the E" allele and serum cholesterol level was not observed in the previously cited studies, in one study 6 the mean serum cholesterol level in patients and controls was highest in E~/~ subjects, lowest in those with E + / + , and intermediate in those with E + /~. This is consistent with the possibility that the EcoRl polymorphism is one among several factors contributing to population variability in serum cholesterol level.…”
Section: Does the Ecorl Polymorphism In The Humansupporting
confidence: 56%
“…This could contribute to the association, in human populations, between CAD and the E" allele, as coronary atherosclerosis is related positively to serum cholesterol concentration. 7 Although a statistically significant association between the E" allele and serum cholesterol level was not observed in the previously cited studies, in one study 6 the mean serum cholesterol level in patients and controls was highest in E~/~ subjects, lowest in those with E + / + , and intermediate in those with E + /~. This is consistent with the possibility that the EcoRl polymorphism is one among several factors contributing to population variability in serum cholesterol level.…”
Section: Does the Ecorl Polymorphism In The Humansupporting
confidence: 56%
“…Bohn and Berg (17) cited significant positive associations between CAD and the Xallele and/or the X-X-genotype in five studies (6-10), and reported that this association was not observed in seven other studies (18)(19)(20)(21)(22)(23)(24). The X-X-genotype was more frequent in Brazilian women with CAD than in control women (25).…”
Section: Discussionmentioning
confidence: 99%
“…Its function as a recognition signal for cellular binding and internalization of LDL particles by the ApoB receptor maintains cholesterol balance in the blood (Disterer et al, 2013;Corsetti et al, 2014). ApoB gene plays the key role in the accumulation of lipid and regulates the balance of cholesterol (Paulweber et al, 1990;Pencina et al, 2015). XbaI locus often has a mutation, which was considered to increase the susceptibility of atherosclerosis of coronary artery (Myant et al, 1989;Genest et al, 1990).…”
Section: Sensitivity Analysismentioning
confidence: 99%